2021
DOI: 10.1200/go.20.00664
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant or Adjuvant Chemotherapy for Breast Cancer in Sub-Saharan Africa: A Retrospective Analysis of Recurrence and Survival in Women Treated for Breast Cancer at the Korle Bu Teaching Hospital in Ghana

Abstract: PURPOSE It is established that addition of systemic therapy to locoregional treatment for breast cancer improves survival. However, reliable data are lacking about the outcomes of such treatment in women with breast cancer in low middle-income countries. We compared the outcomes of treatment in patients who had received neoadjuvant chemotherapy (NACT) or adjuvant chemotherapy and examined the factors associated with breast cancer recurrence and survival at the National Radiotherapy Oncology and Nuclear Medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…It is useful to consider our results in the context of other studies. In comparison to our study (33% of neoadjuvant chemotherapy (NACT) for breast cancer), an analysis of 388 patients with cancer seen from 2005 to 2014 at the National Radiotherapy Oncology and Nuclear Medicine Centre in Ghana showed that 41% of patients with breast cancer received NACT [14]. Our findings are contrary to a study evaluating cancer utilisation in Saudi Arabia that found most chemotherapy to be utilised in neoadjuvant settings [12].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It is useful to consider our results in the context of other studies. In comparison to our study (33% of neoadjuvant chemotherapy (NACT) for breast cancer), an analysis of 388 patients with cancer seen from 2005 to 2014 at the National Radiotherapy Oncology and Nuclear Medicine Centre in Ghana showed that 41% of patients with breast cancer received NACT [14]. Our findings are contrary to a study evaluating cancer utilisation in Saudi Arabia that found most chemotherapy to be utilised in neoadjuvant settings [12].…”
Section: Discussioncontrasting
confidence: 99%
“…Different from a study done in Saudi Arabia looking at the drug utilisation and expenditure of anticancer drugs for breast cancer, 80% of patients utilised fluorouracil, epirubicin and cyclophosphamide (FEC) [ 12 ], in our study ACT was most commonly utilised, which is consistent with current national and international cancer guidelines [ 17 ]. In contrast, regional variation within Africa exists, and a recent study from Ghana found 72% used doxorubicin, cyclophosphamide and fluorouracil, while ACT was only used in 23% [ 14 ]. This study also found most patients had advanced stage presentation, with approximately 73% of breast cancer patients having node positive disease [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation